PENDAMPINGAN ORANG TUA DALAM MENSTIMULUS HAFALAN AL-QUR’AN ANAK - Nurjannah Nurjannah (Pusat Studi Gender dan Anak, 2021)
The problem in this study is the limited time children have in memorizing the Qur'an in formal and non-formal educational institutions. Starting from the closure of schools during the Covid-19 pandemic, the tahfidz program held at SD / MI level schools could not run as usual. So that now children only rely on religious education institutions, namely TPA in memorizing the Qur'an. If it is only done at the TPA, it will be constrained by the limited hours of learning tahfidz. Therefore, to improve the memorization of Juz '30 children, assistance outside of school and TPA is needed, especially at home. In this regard, parents take part in helping children memorize the Koran, namely through muraja'ah assistance by parents. This study aims to analyze the accompaniment of muraja'ah by parents in improving the memorization of Juz 30. This type of research is descriptive and qualitative. The selection of research subjects was done by purposive sampling. Data collection techniques in this study through observation, interviews and documentation. The results of the researcher's findings were that the memorization of juz 30 children gradually increased through muraja'ah assistance by parents at home